The difference between digital educational game and powerpoint-based video on oral hygiene knowledge in children aged 7-8 years: a quasi-experimental - Azarys, Dhefadila Alya Afra; Mona, Deli; Sovira, Gita Dwi Jiwanda; Abdullah, Khatijah Lim (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Oral and dental health problems can be prevented through dental health education in which methods and media play an important role in increasing knowledge. Media that is often used in schools is still conventional, therefore research on modern media use is needed. This study intended to analyze the difference between digital educational games and PowerPoint-based videos in improving oral hygiene knowledge. Methods: This study method was a quasi-experimental with a non-equivalent control group and pretest-posttest design. The study population were 36 second-grade students at Elementary School 20 Kalumbuk, in Padang, Indonesia, selected using total sampling, with inclusion criteria being 7-8 year olds who brought informed consent forms which were already signed by parents and were in good overall health. The sample that met the inclusion criteria was 32 students and were divided into two groups. A total of 16 students in the experimental group (Group A) received oral health education through digital educational game media, while the remaining 16 students in the control group (Group B) were provided with PowerPoint-based video media. Data were collected by giving questionnaires both before and after education. The data analysis was using a paired t-test and an independent t-test. Results: The oral hygiene knowledge average increased 2.94 in Group A and 1.68 in Group B. The paired t-test showed significant improvement in both groups (p = 0.000). The independent t-test revealed a significant difference between digital educational games and PowerPoint-based videos (p = 0.037). Conclusion: There is a significant difference between digital educational games and PowerPoint-based videos in improving dental and oral hygiene knowledge among children aged 7-8 years. The digital educational games demonstrated a higher increase in knowledge compared to the PowerPoint-based videos.